Modification of Lipid A Biosynthesis in Neisseria meningitidis lpxL Mutants: Influence on Lipopolysaccharide Structure, Toxicity, and Adjuvant Activity - van der Ley, Peter (American Society for Microbiology, 2001)
Two genes homologous to lpxL and lpxM from Escherichia coli and other gram-negative bacteria, which are involved in lipid A acyloxyacylation, were identified in Neisseria meningitidis strain H44/76 and insertionally inactivated. Analysis by tandem mass spectrometry showed that one of the resulting mutants, termed lpxL1, makes lipopolysaccharide (LPS) with penta- instead of hexa-acylated lipid A, in which the secondary lauroyl chain is specifically missing from the nonreducing end of the GlcN disaccharide. Insertional inactivation of the other (lpxL2) gene was not possible in wild-type strain H44/76 expressing full-length immunotype L3 lipopolysaccharide (LPS) but could be readily achieved in a galE mutant expressing a truncated oligosaccharide chain. Structural analysis of lpxL2 mutant lipid A showed a major tetra-acylated species lacking both secondary lauroyl chains and a minor penta-acylated species. The lpxL1 mutant LPS has retained adjuvant activity similar to wild-type meningococcal LPS when used for immunization of mice in combination with LPS-deficient outer membrane complexes from N. meningitidis but has reduced toxicity as measured in a tumor necrosis factor alpha induction assay with whole bacteria. In contrast, both adjuvant activity and toxicity of the lpxL2 mutant LPS are strongly reduced. As the combination of reduced toxicity and retained adjuvant activity has not been reported before for either lpxL or lpxM mutants from other bacterial species, our results demonstrate that modification of meningococcal lipid A biosynthesis can lead to novel LPS species more suitable for inclusion in human vaccines.